Arudh, Problematika Dan Solusi Pembumiannya - Muis, Abdul (AL MA'ANY, 2025)
Arudh is a branch of Arabic language science by which the truth or falsity of a poem can be known. Arudh as a science is less noticed by scholars in the North Sumatra region. This research is a literature review research that collects data with documentation studies from both primary and secondary sources with deductive and inductive data analysis. The results of this study are that arudh is a science of Arabic literature but is not as popular as the science of balaghah. The science of arudh is less in demand and less noticed in the treasures of Islamic boarding schools. However, in its development there are several solutions that can be put forward to ground the science of arudh, including: getting used to shalawat and prayers, poetry in the book of lessons, making marches and also making qasidah and songs